Analysis Of The Influence Of The Tourism Sector On Pad Of The Tourism Sub-Sector In The District/City Of The Special Region Of Yogyakarta (2013-2021) - Sultan Sultan; Rakazeta Yusuf Fattah (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
The objective of this study is to examine the impact of variables such as the volume of tourist visit, the quantity of tourist attractions. and the number of non-star hotels on the Original Local Government Revenue (PAD) of the tourism sub sector in the Districts/Cities of the Special Region of Yogyakarta Province in 2013-2021. This research is based on secondary data, namely the number of tourist visits, number of tourist attractions, and local revenue from the tourism sub-sector which is available in the tourism statistics of the Yogyakarta Special Region Tourism Office in 2013-2021 as well as the number of non-star hotels available in the Central Statistics Agency in 2013-2021. The analytical tool used is Panel Data Regression with the Random Effect Model (REM) approach. The research results highlight the positive impact of tourist visits and non-star hotels on local revenue in the tourism sub-sector, emphasizing the need for strategies to increase tourist arrivals and support non-star hotel growth. The lack of influence from tourist attractions suggests a need for further investigation and potential reevaluation of promotional efforts.